Moving towards innovation-driven culture through avenues of creativity - Abas, Nadhratunnaim (Universiti Teknologi MARA, 2010)
As 2010 is announced to be the Year of Innovation and Creativity worldwide, it is a challenge that needs to be faced in order to move forward. Realising this, it is important to educate and expose people to the knowledge of channelling their creative energy through exploration of the Avenues of Creativity in their journey towards innovation. As an observation of the practicality of such exploration, twenty-two first semester students enrolling in the diploma programme of the Business Studies Faculty in Universiti Teknologi MARA (UiTM) Pahang were challenged to produce ideas that would contribute to innovation. Before getting started, they were educated on the knowledge of exploring the Avenues of Creativity. The findings seemed to indicate a positive impact. Four out of five groups of these students managed to produce amazing innovative ideas.